A Phenomenological Study on the School Concept of the Children Attending the Forest School - Berat Ahi; Deniz Kahriman Pamuk (Anı Publishing, 2019)
The current study aims to understand the experiences of the preschool children attending forest school in relation to the school phenomenon. To this end, the current study was conducted on a study group comprised of 32 children. The study was carried out on the basis of the phenomenological model, one of the qualitative research methods. The data of the study were collected through the children's drawings and interviews. The collected data were analyzed by using the triangulation technique, one of the researcher-centered methods built on post-positivist philosophy. As a result of the study, it was concluded that the children perceive the forest as a place and experience it in this way. The forest schools were found to have some strengths in terms of childnature relationship, sense of discovery, friendship relations and the place of the play in the child's school life. Moreover, a significant number of children stated that they feel good in the forest school. On the basis of all these findings, the researchers point out the importance of the studies to be conducted with different associates and it can be argued that the forest school can reshape the phenomenon called the school and that this is worth researching.